2013
DOI: 10.1007/s10459-013-9471-7
|View full text |Cite
|
Sign up to set email alerts
|

Dissonant role perception and paradoxical adjustments: an exploratory study on Medical Residents’ collaboration with Senior Doctors and Head Nurses

Abstract: A good collaboration between health professionals is considered to have benefits for patients, healthcare staff, and organizations. Nevertheless, effective interprofessional collaboration is difficult to achieve. This is particularly true for collaboration between Medical Residents (MRs) and the immediate colleagues they interact with, as Senior Doctors (SDs) and Head Nurses (HNs). Role understanding is one of the factors that may explain difficulties in interprofessional collaboration. Based on this hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 41 publications
0
13
0
1
Order By: Relevance
“… 27 , 28 , 50 , 53–55 , 64 , 77 , 84 , 97 , 109–113 Such hierarchical environments where the rationale for prescribing decisions is rarely discussed are often perceived to contribute to a culture of using doctors-in-training to provide service rather than prioritizing their learning needs ( CMOC 16 in Part S5). 15 , 63 , 110 , 111 , 113–115 …”
Section: Resultsmentioning
confidence: 99%
“… 27 , 28 , 50 , 53–55 , 64 , 77 , 84 , 97 , 109–113 Such hierarchical environments where the rationale for prescribing decisions is rarely discussed are often perceived to contribute to a culture of using doctors-in-training to provide service rather than prioritizing their learning needs ( CMOC 16 in Part S5). 15 , 63 , 110 , 111 , 113–115 …”
Section: Resultsmentioning
confidence: 99%
“…The importance of role understanding as a key facet of interprofessional teamwork is also highlighted in a diverse range of policy and practice drivers (WHO 2010; GMC 2016). A better understanding by medical students of the expertise of nurses in relation to medical practice is important as uncertainty about professional roles which blurs professional boundaries can allow misconception and stereotypes to develop about colleagues from other professions (Fiordelli et al 2014). Challenging professional stereotypes and improving interprofessional working requires a shared understanding of the roles of different professions, as well as a consensus on the delegation of and responsibility for different elements of work (Powell and Davies 2012; Salhani and Coulter 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Fiordelli et al . () found resident doctors felt they were ‘everybody's lackey’ (p. 319) and their most important attributes for success were planning skills and diplomacy with other staff and patients’ families. Residents’ roles in the current study were similarly pressured and time constrained.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, doctors' training prepared them to practise autonomously (Ivory 2015), within an embedded medical hierarchy (Thomson et al 2015). Fiordelli et al (2014) found resident doctors felt they were 'everybody's lackey' (p. 319) and their most important attributes for success were planning skills and diplomacy with other staff and patients' families. Residents' roles in the current study were similarly pressured and time constrained.…”
Section: Discussionmentioning
confidence: 99%